Ultraviolet Radiation Stimulates Activity of CO2 Concentrating Mechanisms in a Bloom-Forming Diatom Under Reduced CO2 Availability - Gao, Guang; Liu, Wei; Zhao, Xin; Gao, Kunshan (Frontiers in Microbiology, 2021)
The diatom Skeletonema costatum is cosmopolitan and forms algal blooms in coastal waters, being exposed to varying levels of solar UV radiation (UVR) and reduced levels of carbon dioxide (CO2). While reduced CO2 availability is known to enhance CO2 concentrating mechanisms (CCMs) in this diatom and others, little is known on the effects of UV on microalgal CCMs, especially when CO2 levels fluctuate in coastal waters. Here, we show that S. costatum upregulated its CCMs in response to UVR (295–395 nm), especially to UVA (320–395 nm) in the presence and absence of photosynthetically active radiation (PAR). The intensity rise of UVA and/or UVR alone resulted in an increase of the activity of extracellular carbonic anhydrase (CAe); and the addition of UVA enhanced the activity of CCMs-related CAe by 23–27% when PAR levels were low. Such UV-stimulated CCMs activity was only significant at the reduced CO2 level (3.4 μmol L−1). In addition, UVA alone drove active HCO3− uptake although it was not as obvious as CAe activity, another evidence for its role in enhancing CCMs activity. In parallel, the addition of UVA enhanced photosynthetic carbon fixation only at the lower CO2 level compared to PAR alone. In the absence of PAR, carbon fixation increased linearly with increased intensities of UVA or UVR regardless of the CO2 levels. These findings imply that during S. costatum blooming period when CO2 and PAR availability becomes lower, solar UVR (mainly UVA) helps to upregulate its CCMs and thus carbon fixation, enabling its success of frequent algal blooms.